Soil organic C stabilization and thresholds in C saturation - Kimetu, J.M.; Lehmann, Johannes; Kinyangi, James; Cheng, C.H.; Thies, J.; Mugendi, D.N.; Pell, A. (Elsevier, 2009)
When building soil organic matter (SOM) contents in agricultural production systems, stabilization of both pre-existing as well as added C is important. A laboratory mineralization experiment was conducted over 374 days to evaluate the effect of pre-existing SOM on soil C mineralization after addition of organic matter (OM) using sugar cane. The SOM gradient used here stretched from 21 to 106 g C kg−1 soil and was a result of different periods of continuous cultivation of 5, 20, 35 and 105 years in comparison to a forest soil. The rate of organic C mineralization was found to be dependent on the status of pre-existing soil organic C (SOC). Highly degraded soil which had been under continuous cultivation for 35 years and more showed the highest rate of C mineralization per unit SOC (117.9 mg C g−1 C) while forest soil had the lowest amount of C mineralized per unit SOC (73.5 mg C g−1 C). Forest soil had the highest amount of increased C mineralization as a result of organic matter (OM) additions (8.0 mg C g−1 soil) followed by the highly degraded soil that had been under cultivation for 105 years (5.5 mg C g−1 soil). Additional mineralized C as a function of time after forest conversion declined progressively within the first 20 years of continuous soil use. Soil which had been under continuous cultivation for 20 years had the lowest amount of additional mineralized C (4.0 mg C g−1 soil). SOM stabilization efficiency in the studied soils appears to be highest with intermediate cultivation history of about 20 years. These soils that have been recently converted to cultivation also appear to have a greater ability to stabilize added OM than the most degraded soils investigated in this study. It is thus advisable to provide intervention strategies to reverse SOM decline for farming communities at an intermediate stage before the soils are highly depleted of SOC.